Differential Subordination and Superordination for Multivalent Functions Associated with Generalized Fox-Wright Functions - Mahmood, Zainab H.; Jassim, Kassim A.; Shihab, Buthyna N. (Iraqi Journal of Science, 2022)
In this paper, we derive some subordination and superordination results for certain subclasses of p− valent analytic functions that defined by generalized Fox-wright functions using the principle of differential subordination, ----------producing best dominant univalent solutions. We have also derived inclusion relations and solved majorization problem.